(untitled) (XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2019)
Decio Gioseffi was the first member of the Scientific Committee of «XY dimensioni del disegno» since the foundation in 1986; his were the first published articles and the fundamental and continuing support for the initiative; so it is auspicious that he would here appear among the first articles of the new «XY» with an unpublished script from 2000, because of the interruption of the publication of the magazine, but strangely anticipating the themes (the image, the models) that will be central in the publishing activity. Propitious was also what Gioseffi wrote in an early number1. «I have the impression that since “XY” began to raise the issue [the] subjects connected with the representation [have become] the favorite subject of each conference or meeting, of any art or science or publication with different humanity, not to say, of every salon conversation.» (Gioseffi 1988, p. 6). May the wish be especially true now for the digital edition. Roberto de Rubertis